Temporal trends in craniopharyngioma management and long‐term endocrine outcomes: A multicentre cross‐sectional study. (29th September 2020) - Hussein, Ziad; Glynn, Nigel; Martin, Niamh; Alkrekshi, Akram; Mendoza, Nigel; Nair, Ramesh; McCullough, Katherine; Marcus, Hani J.; Dorward, Neil; Grieve, Joan; Fersht, Naomi; Dyson, Edward; et al.
Abstract: Background: The optimal management of craniopharyngiomas remains controversial. Objectives: To examine temporal trends in the management of craniopharyngioma with a focus on endocrine outcomes. Methods: This was a cross‐sectional, multicentre study. Patients treated between 1951 and 2015 were identified and divided into four quartiles. Demographics, presentation, treatment and outcomes were collected. Results: In total, 142 patients with childhood‐onset craniopharyngioma (48/142; 34%) and adult‐onset disease (94/142; 66%) were included. The median follow‐up was 15 years (IQR 5‐23 years). Across quartiles, there was a significant trend towards using transsphenoidal surgery ( P < .0001). The overall use of radiotherapy was not different among the four quartiles ( P = .33). At the latest clinical review, the incidence of GH, ACTH, gonadotrophin deficiencies and anterior panhypopituitarism fell significantly across the duration of the study. Anterior panhypopituitarism was not affected by treatment modality (surgery vs surgery and radiotherapy) ( P = .23). There was no difference in the incidence of high BMI (≥25 kg/m 2 ) among the four quartiles ( P = .14). BMI was higher in patients who treated with surgery and radiotherapy than those treated with surgery only ( P = .006). Tumour regrowth occurred in 51 patients (51/142; 36%) with no difference in regrowth among quartiles over the time course of the study ( P = .15). Conclusion: We demonstrate a significant reduction in panhypopituitarism in craniopharyngioma patients over time, most likely because of a trend towards more transsphenoidal surgery. However, long‐term endocrine sequelae remain common and lifelong follow‐up is required.